MANAGEMENT OF VILLAGE FUND ALLOCATION MANAGEMENT TO IMPROVE DEVELOPMENT OF KEMANTREN VILLAGE, BLORA REGENCY, CENTRAL JAVA - Tri Prasetijowati; Bagus Ananda Kurniawan; Ayu Setyaning (DIA: Jurnal Administrasi Publik, 2022)
The Village government in managing village funds Law Number 6 of 2014 concerning villages is a product of the reform era which became the initial form of village independence in government administration and in village financial management. To be able to formulate appropriate financial relationships, it is necessary to understand the authority that belongs to the Village Government. That is, the government budget given by the related Village Head is entirely for development facilities and village empowerment as one of the fair institutions in the form of governance. Based on the results of the study, it can be seen that the management of village fund allocations to improve village development is carried out in several stages, namely the planning, preparation, implementation, management, accountability and supervision stages can be said to have good governance. obstacle.